2006
DOI: 10.1007/s11145-006-9012-3
|View full text |Cite
|
Sign up to set email alerts
|

The influences of language of literacy instruction and vocabulary on the spelling of Spanish–English bilinguals

Abstract: The relation of language of instruction and vocabulary to the English spelling of bilingual first graders receiving either English or Spanish literacy instruction and of monolinguals in English literacy instruction was explored. Only bilingual students in Spanish literacy instruction (SLI) exhibited Spanish-influenced spelling, indicating a powerful effect of language of literacy instruction. SLI without English literacy instruction (ELI) may be a prerequisite for the appearance of Spanish influences in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
2
32
1
Order By: Relevance
“…Most of the previous research on Spanish-English spelling focused on the influence of language transfer (e.g., Cronnell 1985;Escamilla 2006;Fashola et al 1996;Rollo San Francisco et al 2006;Rubin and Carlan 2005;Sun-Alperin and Wang 2008). However, as noted in the previous section, many misspellings, whether they originate in Spanish or English, may not always be transfer exemplars but errors that occur in systematic ways, which are not unique to bilingual spellers.…”
Section: Borrowing and Code-switchingmentioning
confidence: 96%
See 2 more Smart Citations
“…Most of the previous research on Spanish-English spelling focused on the influence of language transfer (e.g., Cronnell 1985;Escamilla 2006;Fashola et al 1996;Rollo San Francisco et al 2006;Rubin and Carlan 2005;Sun-Alperin and Wang 2008). However, as noted in the previous section, many misspellings, whether they originate in Spanish or English, may not always be transfer exemplars but errors that occur in systematic ways, which are not unique to bilingual spellers.…”
Section: Borrowing and Code-switchingmentioning
confidence: 96%
“…Prior spelling research on kindergarten and elementary school-age bilingual students focused primarily on how Spanish language knowledge may influence or transfer to English spelling (Cronnell 1985;Escamilla 2006;Fashola et al 1996;Howard et al 2006;Rollo San Francisco et al 2006;Rubin and Carlan 2005;Sun-Alperin and Wang 2008;Zutell and Allen 1988). Analyzing 27 studies of first language influence on English spelling (languages included Arabic, Cantonese, and Spanish, among others), Figueredo (2006) concluded that the interaction of two languages for transfer of spelling knowledge may be facilitated or hindered by the level and depth of transparencies of the first language writing system to English.…”
Section: Bilingual Influences On Spellingmentioning
confidence: 99%
See 1 more Smart Citation
“…In stark contrast, various aspects of spelling have been extensively studied among English-speaking children (see, e.g., Allal, 1997;Beers & Henderson, 1977;Ehri & Wilce, 1987;Morris, Blanton, Blanton, & Perney, 1995;Perfetti, Rieben, & Fayol, 1997;Read, 1971;Templeton & Morris, 2001;Zutell & Rasinsli, 1989). There have also been a smaller number of studies exploring spelling acquisition among Spanish-speaking children (see, e.g., Carbonell de Grompone, Tuana, Piedra de Moratorio, Lluch de Pintos, & Corbo de Mandracho, 1980;Cuetos, 1993;Defior, Jiménez-Fernández, & Serrano, 2009;Defior, Martos, & Herrera, 2000) and among bilingual children (Arteagoitia, Howard, Loguit, Malabonga, & Kenyon, 2005;Estes & Richards, 2002;San Francisco, Mo, Carlo, August, & Snow, 2006). Adult spelling development, in contrast, has not been rigorously studied (Greenberg, Ehri, & Perin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Alphabetic knowledge and phonemic awareness skills are some examples of skills that transfer positively across alphabetic writing systems (e.g., Cárdenas-Hagan, Carlson, & Pollard-Durodola, 2007;Dickinson, McCabe, Clark-Chiarelli, & Wolf, 2004;Lopez & Greenfield, 2004;Verhoeven, 2007). Negative transfer was observed in L1-influenced orthographic spelling errors (e. g., Bear, Templeton, Helman, & Baren, 2003;Fashola, Drum, Mayer, & Kang, 1996;Ferroli, 1991;Rolla San Francisco, Mo, Carlo, August, & Snow, 2006;Wang & Geva, 2003a, b;Zutell & Allen, 1988). Orthographic mistakes occur when different letters in each language represent the same phoneme.…”
Section: Developmental L1 Spellingmentioning
confidence: 99%